N-distance tests of uniformity on the hypersphere - Bakshaev, A. (Nonlinear Analysis: Modelling and Control, 2010)
In this paper we propose an application of N-distance theory for testing the hypothesis of uniformity on hypersphere S p − 1. The work is a continuation of our research started in [1, 2]. Particular attention is devoted to p = 2, 3 cases. A brief comparative Monte Carlo power study for proposed criteria is provided.
Keywords: tests of uniformity; N-distances